Optical surface devices for atomic and atom physics - Bartoszek, Dobrosława; Fiutowski, Jacek; Dohnalik, Tomasz; Kawalec, Tomasz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
The applications in basic science of optical surface devices for atoms are reviewed, with the emphasis on the optical dipole mirrors. The example of experimental realization of such a mirror constructed in our group is shortly presented. Some methods used in its characterization are shown.
Optica Applicata, Vol. 40, 2010, nr 3, s. 535-546
Keywords: optyka; atom cooling and trapping; optical dipole mirror